Early Reduction of MRI Activity During 6 Months of Treatment With Cladribine Tablets for Highly Active Relapsing Multiple Sclerosis: MAGNIFY-MS. Issue 4 (14th July 2022) - de Stefano, Nicola; Barkhof, Frederik; Montalban, Xavier; Achiron, Anat; Derfuss, Tobias; Chan, Andrew; Hodgkinson, Suzanne; Prat, Alexandre; Leocani, Letizia; Schmierer, Klaus; Sellebjerg, Finn; Vermersch, Patrick; et al.
Abstract : Background and Objectives: The onset of action for high-efficacy immunotherapies in multiple sclerosis (MS) is an important parameter. This study (MAGNIFY-MS) evaluates the onset of action of cladribine tablets by observing changes in combined unique active (CUA) MRI lesion counts during the first 6 months of treatment in patients with highly active relapsing MS. Methods: MRI was performed at screening, baseline, and at months 1, 2, 3, and 6 after initiating treatment with cladribine tablets 3.5 mg/kg. CUA lesion counts, defined as the sum of T1 gadolinium-enhancing (Gd+) lesions and new or enlarging active T2 lesions (without T1 Gd+), were compared between postbaseline and the baseline period and standardized to the period length and the number of MRIs performed. Results: Included in this analysis were 270 patients who received ≥1 dose of cladribine tablets. After treatment initiation, significant reductions in mean CUA lesion counts were observed from month 1 onward compared with the baseline period (−1.193 between month 1 and month 6, −1.500 between month 2 and month 6, and −1.692 between month 3 and month 6; all p < 0.0001). Mean T1 Gd+ lesion counts were decreased from month 2 onward compared with baseline (−0.857 at month 2, −1.355 at month 3, and −1.449 at month 6; all p < 0.0001), whereas the proportion of patients without any CUA lesions increased from 52.0% between month 1 and month 6 to 80.5% between month 3 and month 6. Discussion: Findings suggest an early onset of action for cladribine tablets, with an increasing reduction in active MRI lesions over time. Trial Registration Information: NCT03364036; Date registered: December 06, 2017. Classification of Evidence: Using frequent MRI assessments of the brain over the first 6 months of the MAGNIFY-MS study (NCT03364036), we aimed to determine the onset of action of cladribine tablets 3.5 mg/kg in adult patients with highly active relapsing MS. This study provides Class IV evidence that, in such patients, treatment with cladribine tablets is associated with an early onset of action with reductions in active MRI lesion counts from month 2 (day 60) onward, with an increasing reduction in such lesions over time.